Detection of Synaptic Proteins in Microglia by Flow Cytometry - Brioschi, Simone; d’Errico, Paolo; Amann, Lukas S.; Janova, Hana; Wojcik, Sonja M.; Meyer-Luehmann, Melanie; Rajendran, Lawrence; Wieghofer, Peter; Paolicelli, Rosa C.; Biber, Knut (Frontiers in Molecular Neuroscience, 2020)
A growing body of evidence indicates that microglia actively remove synapses in vivo, thereby playing a key role in synaptic refinement and modulation of brain connectivity. This phenomenon was mainly investigated in immunofluorescence staining and confocal microscopy. However, a quantification of synaptic material in microglia using these techniques is extremely time-consuming and labor-intensive. To address this issue, we aimed to quantify synaptic proteins in microglia using flow cytometry. With this approach, we first showed that microglia from the healthy adult mouse brain contain a detectable level of VGLUT1 protein. Next, we found more than two-fold increased VGLUT1 immunoreactivity in microglia from the developing brain (P15) as compared to adult microglia. These data indicate that microglia-mediated synaptic pruning mostly occurs during the brain developmental period. We then quantified the VGLUT1 staining in microglia in two transgenic models characterized by pathological microglia-mediated synaptic pruning. In the 5xFAD mouse model of Alzheimer Disease microglia exhibited a significant increase in VGLUT1 immunoreactivity before the onset of amyloid pathology. Moreover, conditional deletion of TDP-43 in microglia, which causes a hyper-phagocytic phenotype associated with synaptic loss, also resulted in increased VGLUT1 immunoreactivity within microglia. This work provides a quantitative assessment of synaptic proteins in microglia, under homeostasis and in mouse models of disease.